Debondable solvent-based pressure sensitive adhesives (PSA)
By developing a debondable solvent-based pressure-sensitive adhesive composition containing (meth)acrylate copolymer, electrolyte, crosslinking agent and solvent, the problem of difficulty in disassembling adhesive-bonded articles in the prior art without damaging the substrate is solved, and an efficient and clean debonding effect on metal and glass substrates is achieved.
Patent Information
- Application Number
- CN202380063292.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Priority Date
- 2022-09-05
- Filing Date
- 2023-08-23
- Publication Date
- 2025-04-11
AI Technical Summary
The prior art is difficult to effectively disassemble adhesive-bonded articles without damaging the substrate, especially on metal substrates and glass substrates, and traditional mechanical disassembly or chemical erosion methods pose a risk of damage to the substrate.
A debondable solvent-based pressure-sensitive adhesive composition is developed, which comprises (meth)acrylate copolymer, electrolyte, crosslinking agent and solvent, capable of efficient and clean debonding upon application of voltage.
The composition provides high stability and high bond strength on metal substrates and glass substrates, and enables effective debonding when voltage is applied, avoiding damage to the substrate.
Smart Images

Figure BDA0005293630030000061 
Figure BDA0005293630030000111 
Figure BDA0005293630030000121
Abstract
Description
Technical Field
[0001] The present invention relates to a solvent-based pressure-sensitive adhesive composition that can be debonded from a particular substrate to which it is applied. The present invention relates to a debondable solvent-based pressure-sensitive adhesive composition comprising the following ingredients: a) (meth)acrylate copolymer; b) electrolyte; c) crosslinking agent; and d) solvent. Background Art
[0002] Adhesive bonding and polymer coatings are commonly used in the assembly and finishing of manufactured products. They are used to replace mechanical fasteners such as screws, bolts, and rivets to provide bonding with reduced machine costs and greater applicability in the manufacturing process. Adhesive bonding distributes stress evenly, reduces the possibility of fatigue, and seals joints from corrosive substances.
[0003] While adhesive bonding thus offers many advantages over mechanical fasteners, adhesively bonded items tend to be difficult to disassemble when necessary in practical applications. Adhesive removal by mechanical methods (such as by sandblasting or by wire brushing) is generally excluded, in part because the adhesive is disposed between the substrates and is therefore difficult to access or to abrade without damaging the substrate surface. Disassembly by application of chemicals and / or elevated temperatures may be effective but can be time-consuming and complicated to perform; moreover, the aggressive chemicals and / or harsh conditions required can damage the separated substrates, rendering them unsuitable for subsequent applications.
[0004] With these problems in mind, some authors have attempted to develop electrochemically debondable adhesive compositions in which an electric current is passed through a dried or cured composition to break the bond at the adhesive-substrate interface.
[0005] WO2007 / 142600 describes an electrochemically weakenable adhesive composition which provides an adhesive bond to a conductive surface and an ionic conductivity sufficient to achieve weakening of the adhesive bond when a voltage is applied across the adhesive composition, wherein the composition comprises an effective amount of at least one ionic compound to impart the ionic conductivity, and wherein the melting point of the ionic compound is no greater than 120°C.
[0006] US2007 / 0269659 describes an adhesive composition that is debondable at two interfaces, which composition: (i) comprises a polymer and an electrolyte; (ii) promotes bonding of the two surfaces; and (iii) responds to a voltage applied across the two surfaces to form an anode interface and a cathode interface, thereby debonding from both the anode surface and the cathode surface.
[0007] US2008 / 0196828 describes a hot melt adhesive composition comprising: a thermoplastic component; and an electrolyte, wherein the electrolyte provides the composition with sufficient ionic conductivity to enable a Faradaic reaction at a bond formed between the composition and a conductive surface and to debond the composition from the surface.
[0008] U.S. Patent No. 7,465,492 describes an electrochemically debondable composition comprising: a matrix functional group comprising a monomer selected from the group consisting of acrylic, methacrylic, and combinations thereof; a free radical initiator; and an electrolyte, wherein the electrolyte provides sufficient ionic conductivity to the composition to support a Faradaic reaction at a bond formed between the composition and a conductive surface and thereby allow the composition to be debonded from the surface. In this citation, the electrolyte comprises a salt that is capable of being solvated into the composition and is a member of the group consisting of perchlorate, tetrafluoroborate, hexafluorophosphate, trifluoromethanesulfonate, and ammonium (NH ) anions of triflimide. 4 + ) salt, alkali metal salt, alkaline earth metal salt or rare earth metal salt.
[0009] EP 3363875 provides an electrically strippable adhesive composition which forms an adhesive layer having high adhesiveness and can be easily stripped when a voltage is applied for a short time. The electrically strippable adhesive composition of the invention comprises a polymer and 0.5-30 wt % of an ionic liquid based on the weight of the polymer, wherein the anion of the ionic liquid is a bis(fluorosulfonyl)imide anion.
[0010] WO2017 / 133864 describes a method for reversibly bonding a first substrate and a second substrate, wherein at least the first substrate is a non-conductive substrate, the method comprising: a) coating the surface of one or more non-conductive substrates with a conductive ink; b) applying an electrically debondable hot melt adhesive composition to the surface of the first substrate coated with the conductive ink and / or the second substrate; c) contacting the first substrate with the second substrate so that the electrically debondable hot melt adhesive composition is sandwiched between the two substrates; d) forming an adhesive bond between the two substrates to provide a bonded substrate; and e) applying a voltage to the bonded substrates, whereby the adhesion at the interface between the electrically debondable hot melt adhesive composition and the substrate surface is significantly weakened.
[0011] Therefore, there is a need for debondable solvent-based pressure sensitive adhesives that provide high stability and high bond strength on metal and glass substrates while enabling efficient and clean debonding upon application of voltage. Summary of the invention
[0012] The present invention relates to a debondable solvent-based pressure-sensitive adhesive composition, which comprises: a) a (meth)acrylate copolymer, which is formed from monomers selected from the group consisting of ethyl (meth)acrylate, methyl acrylate, 2-ethylhexyl (meth)acrylate, 3-epoxypropyl (meth)acrylate, 2-hydroxyethyl (meth)acrylate, hydrogenated polybutadiene (meth)acrylate, glacial acrylic acid, vinyl acetate, and mixtures thereof; b) an electrolyte selected from the group consisting of 1-butyl-3-methylimidazolium bis(trifluoromethylsulfonyl)imide, 1-ethyl-3-vinylimidazolium methane sulfonate, 1-dodecyl-3-methylimidazolium bis(trifluoromethylsulfonyl)imide, tributyl (ethyl)phosphonium diethyl phosphate, trihexyltetradecylphosphonium bis(trifluoromethylsulfonyl)amide, and mixtures thereof; c) a crosslinking agent; and d) a solvent.
[0013] The present invention also relates to a dry film formed from the debondable solvent-based pressure-sensitive adhesive composition according to the present invention.
[0014] The present invention encompasses the use of the debondable solvent-based pressure-sensitive adhesive composition or dry film according to the present invention in an electronic device.
[0015] The present invention also encompasses a bonded structure comprising: a) a first substrate having a conductive surface; and b) a second substrate having a conductive surface; wherein the debondable pressure-sensitive adhesive or dry film according to the present invention is disposed between the conductive surfaces of the first substrate and the second substrate.
[0016] Furthermore, the present invention relates to a method for debonding a bonded structure according to the present invention, the method comprising the following steps: 1) applying a voltage across two surfaces to form an anodic interface and a cathodic interface, preferably applying a voltage of 0.5 to 200 V for 1 second to 60 minutes; and 2) debonding the surfaces. BRIEF DESCRIPTION OF THE DRAWINGS
[0017] Figure 1 The bonded structure is shown.
[0018] Figure 2 A debonded structure is shown.
[0019] Figure 3 The bonded structure is shown.
[0020] Figure 4 A debonded structure is shown.
[0021] Figure 5 The force required to pull apart aluminum foils bonded together using the compositions according to Example 1 and Comparative Example 4 is shown.
[0022] Figure 6 The force required to pull apart aluminum foils bonded together using the compositions according to Example 2 and Comparative Example 5 is shown.
[0023] Figure 7 The force required to pull apart aluminum foils bonded together using the compositions according to Example 3 and Comparative Example 6 is shown.
[0024] Figure 8 The force required to pull apart aluminum foils bonded together using the composition according to Example 7 is shown. DETAILED DESCRIPTION
[0025] In the following paragraphs, the present invention is described in more detail. Unless explicitly indicated to the contrary, each aspect described in this way can be combined with any other one or more aspects. In particular, any feature indicated as being preferred or advantageous can be combined with any other one or more features indicated as being preferred or advantageous.
[0026] Unless the context dictates otherwise, in the context of the present invention, the terms used should be interpreted according to the following definitions.
[0027] As used herein, the singular forms "a," "an," and "the" include both singular and plural referents unless the context clearly dictates otherwise.
[0028] As used herein, the terms "comprising / comprises / comprised of" are synonymous with "including / includes" or "containing / contains," are inclusive or open-ended, and do not exclude additional unrecited members, elements, or method steps. If used, the phrase "consisting of is closed-ended and excludes all additional elements. Furthermore, the phrase "consisting essentially of excludes additional essential elements, but allows for the inclusion of insubstantial elements that do not materially change the nature of the invention.
[0029] The references to numerical endpoints include all numbers and fractions subsumed within the respective ranges, as well as the recited endpoints.
[0030] Unless otherwise specified, all percentages, parts, ratios, etc. mentioned herein are based on weight.
[0031] When an amount, concentration, or other value or parameter is expressed in the form of a range, a preferred range, or a preferred upper value and a preferred lower value, it should be understood that any range that can be obtained by combining any upper value or preferred value with any lower value or preferred value is also specifically disclosed, regardless of whether the obtained range is explicitly mentioned in the context.
[0032] The terms "preferred / preferably", "desirable", "particular / particularly", and their synonyms are generally used herein to refer to embodiments of the present disclosure that may provide particular benefits in certain circumstances. However, the recitation of one or more preferred, preferred, desired, or particular embodiments does not mean that other embodiments are not useful, and is not intended to exclude those other embodiments from the scope of the present disclosure.
[0033] As used throughout this application, the words "may" are used in a permissive sense (ie, meaning having the potential to), rather than in a mandatory sense.
[0034] As used herein, the term "electrochemically debondable" means that after the pressure-sensitive adhesive is cured, the bond strength can be weakened by at least 50% after applying a potential of 30V for a duration of up to 30 minutes. The pressure-sensitive adhesive is applied between two aluminum foils bonded by the adhesive so that an electric current flows through the adhesive bonding layer. The bond strength is measured by peeling adhesion test (180°) according to FTM-1 in the FINAT Technical Manual 9th Edition with slight modifications (mainly, a speed of 200 mm / min, an adhesive thickness of 30 μm, and a sample width of 25 mm).
[0035] As used herein, the term "clean debonding" means that after debonding, the solvent-based pressure-sensitive adhesive composition is only on the first substrate or the second substrate, which means that one of the substrates is substantially free of adhesive. The term "substantially free of adhesive" means herein that 5% or less, preferably less than 3%, more preferably less than 1% of adhesive is left in the substrate after debonding, wherein visual inspection / evaluation is performed.
[0036] As used herein, the term "monomer" refers to a substance that can undergo polymerization to provide a building block for the chemical structure of a polymer. As used herein, the term "monofunctional" refers to having one polymerizable moiety. As used herein, the term "multifunctional" refers to having more than one polymerizable moiety.
[0037] As used herein, "(meth)acryl" is a shorthand term for "acryl" and / or "methacryl." Thus, the term "(meth)acrylamide" refers collectively to acrylamide and methacrylamide.
[0038] The term "pressure sensitive adhesive" or "PSA" is used herein to refer to a class of adhesives that form a bond when pressure is applied to cause the adhesive to bond to a surface.
[0039] All references cited in this specification are hereby incorporated by reference in their entirety.
[0040] Unless otherwise defined, all terms (including technical and scientific terms) used in disclosing the present invention have the meanings commonly understood by ordinary technicians in the field to which the present invention belongs. By way of further guidance, the definitions of terms are included to better understand the teachings of the present invention.
[0041] The present invention relates to a debondable solvent-based pressure-sensitive adhesive composition, which comprises: a) a (meth)acrylate copolymer, wherein the (meth)acrylate copolymer is formed from monomers selected from the group consisting of ethyl (meth)acrylate, methyl acrylate, butyl (meth)acrylate, 2-ethylhexyl (meth)acrylate, 3-epoxypropyl (meth)acrylate, 2-hydroxyethyl (meth)acrylate, hydrogenated polybutadiene (meth)acrylate, glacial acrylic acid, vinyl acetate, and mixtures thereof; b) an electrolyte selected from the group consisting of 1-butyl-3-methylimidazolium bis(trifluoromethylsulfonyl)imide, 1-ethyl-3-vinylimidazolium methane sulfonate, 1-dodecyl-3-methylimidazolium bis(trifluoromethylsulfonyl)imide, tributyl (ethyl)phosphonium diethyl phosphate, trihexyltetradecylphosphonium bis(trifluoromethylsulfonyl)amide, and mixtures thereof; c) a crosslinking agent; and d) a solvent.
[0042] The debondable solvent-based pressure-sensitive adhesive composition according to the present invention provides high stability and high bond strength on metal substrates, especially steel and glass substrates, while enabling efficient and clean debonding upon application of voltage.
[0043] The debondable solvent-based pressure-sensitive adhesive composition according to the present invention comprises a (meth)acrylate copolymer. The (meth)acrylate copolymer is formed by monomers selected from the group consisting of ethyl (meth)acrylate, methyl acrylate, butyl (meth)acrylate, 2-ethylhexyl (meth)acrylate, 3-epoxypropyl (meth)acrylate, 2-hydroxyethyl (meth)acrylate, hydrogenated polybutadiene (meth)acrylate, glacial acrylic acid, vinyl acetate, and mixtures thereof.
[0044] These monomers are preferred because their combination provides good adhesion strength and good bonding strength on metal substrates and glass substrates.
[0045] In one embodiment, the (meth)acrylate copolymer is formed from three or more monomers selected from the group consisting of ethyl (meth)acrylate, methyl acrylate, butyl (meth)acrylate, 2-ethylhexyl (meth)acrylate, 3-epoxypropyl (meth)acrylate, 2-hydroxyethyl (meth)acrylate, hydrogenated polybutadiene (meth)acrylate, glacial acrylic acid, vinyl acetate, and mixtures thereof.
[0046] In another embodiment, the (meth)acrylate copolymer is formed from four or more monomers selected from the group consisting of ethyl (meth)acrylate, methyl acrylate, butyl (meth)acrylate, 2-ethylhexyl (meth)acrylate, 3-epoxypropyl (meth)acrylate, 2-hydroxyethyl (meth)acrylate, hydrogenated polybutadiene (meth)acrylate, glacial acrylic acid, vinyl acetate, and mixtures thereof.
[0047] The use of three or more or four or more different monomers having different Tg's and / or functionalities enables fine tuning of the adhesive and cohesive strength properties of the final (meth)acrylate copolymer.
[0048] Commercially available (meth)acrylate monomers suitable for use in the present invention include, but are not limited to: ethyl acrylate and 2-ethylhexyl acrylate from BASF; and 3-epoxypropyl methacrylate from ARPADIS.
[0049] The (meth)acrylate copolymer may be present in the debondable solvent-based pressure-sensitive adhesive composition according to the present invention in an amount of 23% to 55%, preferably 25% to 40%, more preferably 26% to 39%, based on the total weight of the composition.
[0050] A lower amount of the (meth)acrylate copolymer results in poor adhesive properties and is detrimental to film-forming properties, whereas a too high amount results in poor processability.
[0051] The (meth)acrylate copolymer can be obtained by any known polymerization method, among which mention can be made of: solution polymerization in the presence of an organic solvent in which the obtained copolymer can be dissolved; suspension polymerization; bulk polymerization; emulsion polymerization; and mini-emulsion polymerization. From the viewpoint of yield or productivity and the resulting properties of the coating film derived from the copolymer, solution polymerization is preferably used herein. In any of these methods, the polymerization temperature will generally be in the range of 30° C. to 120° C.: the temperature does not have to be kept constant, but can, for example, be increased during the polymerization.
[0052] The polymerization will conventionally be carried out using a free radical initiator (typically in an amount of 0.05 to 5% by weight based on the total weight of the monomers used). Suitable free radical initiators include: hydrogen peroxide; alkyl hydroperoxides such as tert-butyl hydroperoxide and cumene hydroperoxide; persulfates such as ammonium persulfate, potassium persulfate and sodium persulfate; organic peroxides such as acyl peroxides and including benzoyl peroxide; dialkyl peroxides such as di-tert-butyl peroxide; peroxyesters such as tert-butyl perbenzoate; and azo functional initiators such as azobis(isobutyronitrile) (AIBN), 2,2'-azobis(2-methylbutyronitrile) (AMBN) and 4,4'-azobis(4-cyanovaleric acid).
[0053] The above peroxy initiator compounds can in some cases be advantageously used in combination with a suitable reducing agent to form a redox system. As suitable reducing agents, mention may be made of: sodium pyrosulfite; potassium pyrosulfite; sodium bisulfite; potassium hydrogen sulfate; acetone bisulfite; hydroxymethanesulfinic acid; and isoascorbic acid. Metal compounds such as Fe.EDTA can also be usefully used as part of the redox initiator system.
[0054] A person skilled in the art will be able to choose an appropriate scheme for adding the initiator to the polymerization vessel during the polymerization. It can be introduced completely into the polymerization vessel or used continuously or in stages according to its consumption during the free radical polymerization. Preferably, a portion is initially charged and the remainder is provided according to the consumption of the polymerization.
[0055] Chain transfer agents may also be present in the polymerization mixture (typically in amounts of 0.01 to 1 wt % based on the total weight of monomers used). Exemplary chain transfer agents: mercaptans such as n-dodecyl mercaptan; thioglycolates such as octyl thioglycolate; α-methylstyrene dimer; and terpinolene.
[0056] The debondable solvent-based pressure-sensitive adhesive composition according to the present invention comprises an electrolyte. The electrolyte comprises at least one salt according to formula (I) or formula (II), or consists of a salt according to formula (I) or formula (II):
[0057]
[0058] Where: R 1 , R 2 , R 3 , R 4 and R 5 are independently selected from hydrogen, C 1 -C 18 Alkyl, C 3 -C 18 Cycloalkyl, C 6 -C 18
[0059] Aryl, C 7 -C 24 Aralkyl, C 2 -C 20 Alkenyl, -C(O)R q , -C(O)OH, -CN, or -NO 2 ;
[0060] R q It is C 1 -C 6 Alkyl; and
[0061] X - It is a counter anion.
[0062] The electrolyte is selected from 1-butyl-3-methylimidazolium bis(trifluoromethylsulfonyl)imide, 1-ethyl-3-vinylimidazolium methane sulfonate, 1-dodecyl-3-methylimidazolium bis(trifluoromethylsulfonyl)imide, tributyl(ethyl)phosphonium diethyl phosphate, trihexyltetradecylphosphonium bis(trifluoromethylsulfonyl)amide, and mixtures thereof.
[0063] The above-mentioned electrolytes are preferred because they have good solubility for the (meth)acrylate copolymer.
[0064] Commercially available electrolytes suitable for use in the present invention include, but are not limited to: 1-butyl-3-methylimidazolium bis(trifluoromethylsulfonyl)imide (BMIM NTF) from Sigma Aldrich; Cyphos IL 109 and Cyphos IL 169 from Solvay; and 1-dodecyl-3-methylimidazolium bis(trifluoromethylsulfonyl)imide from Iolitec.
[0065] The electrolyte may be present in the debondable solvent-based pressure-sensitive adhesive composition according to the present invention in an amount of 0.1 to 12%, preferably 0.4 to 11%, more preferably 0.5 to 11%, even more preferably 0.75 to 10.75%, based on the total weight of the composition.
[0066] These amounts of electrolyte are preferred because an amount greater than 12% results in good debonding effect, but curing will be incomplete and thus initial adhesive properties will be adversely affected; whereas a small amount (mainly, less than 0.1%) results in a lack of debonding effect.
[0067] The debondable solvent-based pressure-sensitive adhesive composition according to the present invention comprises a crosslinking agent. Preferably, the crosslinking agent is a metal chelate crosslinking agent. The crosslinking agent suitable for the present invention should be stable at a temperature of -20°C to 100°C.
[0068] The crosslinking agent suitable for use in the present invention is preferably a coordination compound of: i) a metal selected from Al, Ti, Fe, Co, Ba, Zr, K and Zn; and ii) an organic compound providing a 1,3-dicarbonyl ligand.
[0069] The metal is selected from Al, Ti, Fe, Co, Ba, Zr, K and Zn; preferably, the metal is Al or Ti. As used herein, an organic compound providing a 1,3-dicarbonyl ligand is a compound that is capable of participating in chelation with a metal and has at least two carbonyl groups arranged in a 1,3 spatial arrangement relative to the carbon atom to which they are bonded.
[0070] Exemplary metal chelates of this type include, but are not limited to, metal β-ketoesters, such as metal acetoacetates, including metal ethyl acetoacetate (ligand: ethyl acetoacetate); metal malonates, such as metal diethyl malonate; metal acetylacetonate (ligand: acetylacetone); metal formylacetonate (ligand: formylacetone); and metal formylacetophenonate (ligand: formylacetophenonate).
[0071] Preferably, the crosslinking agent is selected from aluminum tris-2,4-pentanedionate, diisopropoxybis(acetylacetonate)titanium, and mixtures thereof.
[0072] These crosslinkers are preferred because they have a positive impact on the final cohesion of the composition prior to application of a voltage.
[0073] Commercially available crosslinking agents suitable for use in the present invention include, but are not limited to, aluminum tris-2,4-pentanedionate and titanium diisopropoxybis(acetylacetonate) from Siccanor.
[0074] The crosslinking agent may be present in the debondable solvent-based pressure-sensitive adhesive composition according to the present invention in an amount of 0.01% to 1.0%, preferably 0.02% to 0.75%, more preferably 0.03% to 0.65%, based on the total weight of the composition.
[0075] The amount of crosslinker has an effect on the adhesion and cohesion of the composition. When the amount of crosslinker is low, the PSA will be too soft and unable to hold the two substrates together, while too high an amount will result in a PSA that is not flexible enough to wet out on the surface and establish good contact.
[0076] The debondable solvent-based pressure-sensitive adhesive composition according to the present invention comprises a solvent to adjust its viscosity. Preferably, the solvent is a mixture of two or more solvents, more preferably a mixture of three or more solvents. Preferably, the solvent is selected from methyl acetate, ethyl acetate, isobutyl acetate, n-butyl acetate, methanol, ethanol, isopropanol, pentanedione, hexane, heptane, toluene, acetone, and mixtures thereof.
[0077] These solvents are preferred because they maintain the viscosity of the PSA within the target range and aid in shaping the (meth)acrylate copolymer.
[0078] In one embodiment, the solvent is a mixture of two or more solvents selected from methyl acetate, ethyl acetate, isobutyl acetate, n-butyl acetate, methanol, ethanol, isopropanol, pentanedione, hexane, heptane, toluene, acetone, and mixtures thereof.
[0079] In another embodiment, the solvent is a mixture of three or more solvents selected from methyl acetate, ethyl acetate, isobutyl acetate, n-butyl acetate, methanol, ethanol, isopropanol, pentanedione, hexane, heptane, toluene, acetone, and mixtures thereof.
[0080] Commercially available solvents suitable for use in the present invention include, but are not limited to: ethyl acetate from Eastman; and isopropyl alcohol from Shell.
[0081] The solvent may be present in the debondable solvent-based pressure-sensitive adhesive composition according to the present invention in an amount of 43% to 65%, preferably 44% to 62%, more preferably 45% to 60%, based on the total weight of the composition.
[0082] The solvent affects the viscosity of the composition and thus the processability of the composition. If the amount of solvent is too low, it will lead to too high a viscosity, which will cause problems with processability; while too high an amount will lead to too low a viscosity and adversely affect other properties.
[0083] Commercially available (meth)acrylate copolymers (including solvents and crosslinkers) suitable for use in the present invention include, but are not limited to: Loctite DURO-TAK 183A available from Henkel Corporation; DURO-TAK 195A available from Henkel Corporation; and DURO-TAK AH115 EU available from Henkel Corporation.
[0084] The debondable solvent-based pressure-sensitive adhesive composition according to the present invention may further comprise a tackifier. The tackifier helps balance the adhesive and cohesive properties of the PSA by increasing the peel and tack of the PSA.
[0085] Preferably, the tackifier is selected from aliphatic petroleum hydrocarbon resins, alicyclic petroleum hydrocarbon resins, aromatic petroleum hydrocarbon resins and hydrogenated derivatives thereof; polycyclopentadiene resins, hydrogenated polycyclopentadiene resins, aromatic modified hydrogenated polycyclopentadiene resins; terpenes, aromatic terpenes, hydrogenated terpenes; polyterpenes, aromatic modified polyterpenes and terpene phenolic resins; copolymers of α-methylstyrene and vinyl aromatic monomers; gum rosin, gum rosin esters, wood rosin, wood rosin esters, tall oil rosin, tall oil rosin esters and hydrogenated rosin esters; and mixtures thereof, more preferably, the tackifier is selected from glycerol esters of partially hydrogenated gum rosin, aliphatic C5 petroleum hydrocarbon resins, and mixtures thereof.
[0086] These tackifiers are preferred because they are compatible with the (meth)acrylate copolymers and thus result in the desired tack.
[0087] Commercially available tackifiers suitable for use in the present invention include, but are not limited to: Hydrogral G from DRT Corporation; and M-110 and M-120 Hydrogenated C available from Arakawa Chemical. 5 and / or C 9 Hydrocarbon raw materials.
[0088] The tackifier may be present in the debondable solvent-based pressure-sensitive adhesive composition according to the present invention in an amount of 5 to 15%, preferably 7 to 14%, more preferably 9 to 13%, based on the total weight of the composition.
[0089] This range of amounts has been found to be ideal for the compositions according to the invention, with less than 5% resulting in insufficient tack, while too high an amount (over 15%) resulting in excessive tack and adversely affecting other properties of the composition.
[0090] The debondable solvent-based pressure-sensitive adhesive composition according to the present invention may further comprise a stabilizer. Preferably, the stabilizer is selected from: 1,3,5-trimethyl-2,4,6-tris(3,5-di-tert-butyl-4-hydroxybenzyl)benzene, pentaerythritol tetra-3(3,5-di-tert-butyl-4-hydroxybenzyl)propionate, n-octadecyl-3(3,5-di-tert-butyl-4-hydroxybenzyl)propionate, 4,4'-methylenebis(2,6-tert-butylphenol), 4,4'-thiobis(6-tert-butyl-o-methylbenzyl)propionate, phenol), 2,6-tert-butylphenol, 6-(4-hydroxyphenoxy)-2,4-bis(n-octyl-thio)-1,3,5-triazine, di-n-octadecyl 3,5-di-tert-butyl-4-hydroxy-benzylphosphonate, 2-(n-octylthio)ethyl 3,5-di-tert-butyl-4-hydroxybenzoate and sorbitol hexa([3-(3,5-di-tert-butyl-4-hydroxyphenyl)-propionate], and mixtures thereof.
[0091] It has been found that the stabilizers listed above provide good protection for the (meth)acrylate copolymers from thermal degradation.
[0092] Commercially available stabilizers suitable for use in the present invention include, but are not limited to, Irganox 1010 and Irganox B225 from BASF.
[0093] The stabilizer may be present in the debondable solvent-based pressure-sensitive adhesive composition according to the present invention in an amount of 0.05% to 0.25%, preferably 0.08% to 0.2%, based on the total weight of the composition.
[0094] If the amount of the stabilizer is less than 0.05%, this may result in insufficient stabilizing properties, whereas too high an amount may result in adverse effects on other properties of the composition.
[0095] Of course, the solvent-based pressure-sensitive adhesive composition according to the present invention may also contain standard additives, such as: polar rubber; pigment; filler; plasticizer; leveling agent; foam inhibitor; and rheology control agent. The choice of suitable additives is only limited by: these must be compatible with the other components of the composition and cannot be harmful to the use of the composition.
[0096] The present invention relates to a dry film formed from the debondable solvent-based pressure-sensitive adhesive composition according to the present invention.
[0097] The thickness of the dry film according to the present invention is preferably 2 μm to 150 μm.
[0098] The dry film is obtained by applying the composition on a release liner, such as silicone foil, and then heating it for 3 minutes at 110° C. During the heating process, the solvent evaporates and a substantially solvent-free dry film is left.
[0099] The term substantially free of solvent means that the dry film comprises less than 1.5%, preferably less than 1.0%, more preferably less than 0.1%, even more preferably less than 0.01% solvent, based on the total weight of the dry film.
[0100] The present invention relates to the use of the debondable solvent-based pressure-sensitive adhesive composition or the dry film according to the present invention in electronic devices.
[0101] Non-limiting examples of suitable electronic devices are smartphones, tablets, computers, other handheld devices, and displays.
[0102] Non-limiting examples of potential uses are frame to housing (front glass to back glass) applications and battery removal applications.
[0103] The present invention relates to a bonded structure comprising: a) a first substrate having a conductive surface; and b) a second substrate having a conductive surface; wherein the debondable solvent-based pressure-sensitive adhesive composition or dry film according to the present invention is disposed between the conductive surfaces of the first substrate and the second substrate.
[0104] When the debondable solvent-based pressure-sensitive adhesive composition is disposed between the conductive surface of the first substrate and the second substrate, it is first disposed on the conductive surface of the first substrate and dried at 110° C. for 3 minutes to obtain a dry pressure-sensitive adhesive film. Subsequently, the conductive surface of the second substrate is placed on top of the dry pressure-sensitive adhesive film, and pressure is then applied to form a bonded structure.
[0105] As attached Figure 1 As shown in the figure, a bonded structure is provided in which a layer (10) of a debondable solvent-based pressure-sensitive adhesive composition is disposed between two conductive substrates (11). Each layer of the conductive substrate (11) is in electrical contact with a power source (13), which can be a battery or an AC-driven direct current (DC) source. The positive and negative terminals of the power source (13) are shown in a fixed position, but those skilled in the art will of course recognize that the polarity of the system can be reversed.
[0106] Two conductive substrates (11) are shown in the form of layers, which may consist in particular of: a metal film; a metal sheet; a metal mesh or grid; deposited metal particles; a resin material, which is made conductive by a conductive element disposed therein; or a conductive oxide layer. As exemplary conductive elements, silver filaments, single-walled carbon nanotubes and multi-walled carbon nanotubes may be mentioned. As exemplary conductive oxides, doped indium oxides, such as indium tin oxide (ITO); doped zinc oxide; antimony tin oxide; cadmium stannate; and zinc stannate may be mentioned. In addition to the choice of conductive material, a person skilled in the art will recognize that in the case where the conductive substrate (11) is in the form of a grid or mesh, which provides limited contact with the cured adhesive layer (10), the effectiveness of the debonding operation may be reduced.
[0107] The present invention relates to a method for debonding the bonded structure according to the present invention, the method comprising the following steps: 1) applying a voltage across two surfaces to form an anodic interface and a cathodic interface, preferably applying a voltage of 0.5 to 200 V for 1 second to 60 minutes; and 2) debonding the surfaces.
[0108] When a voltage is applied between each conductive substrate (11), current is supplied to the debondable solvent-based pressure-sensitive adhesive composition (10) disposed therebetween. This initiates an electrochemical reaction at the interface of the substrate (11) and the adhesive composition, which should be understood to be oxidative at the positively charged interface or anodic interface and reductive at the negatively charged interface or cathodic interface. This reaction is believed to weaken the adhesive bond between the substrates, thereby allowing the debondable composition to be easily removed from the substrates.
[0109] like Figure 2 As shown in , debonding occurs at the positive electrode interface, i.e., the interface between the debonded solvent-based pressure-sensitive adhesive composition (10) and the conductive surface (11) in electrical contact with the positive electrode. The adhesive bond at the interface of the two substrates can be weakened by reversing the direction of the current before separating the substrates.
[0110] However, it should be noted that the composition of the pressure-sensitive adhesive layer (10) can be adjusted so that debonding occurs at the positive electrode interface or the negative electrode interface or from both simultaneously. For some embodiments, the voltage applied across the two surfaces to form the anode interface and the cathode interface will cause debonding to occur simultaneously at the anode and cathode adhesive / substrate interfaces. In an alternative embodiment, if the composition is not responsive to direct current at both interfaces, the reversed polarity can be used to debond the two substrate / adhesive interfaces simultaneously. The current can be applied with any suitable waveform, provided that the debonding is allowed to proceed for a sufficient total time at each polarity. In this regard, sinusoidal waveforms, rectangular waveforms, and triangular waveforms may be suitable and may be applied by a controlled voltage source or a controlled current source.
[0111] Without intending to limit the present invention, it is believed that the debonding operation can be effectively performed when at least one and preferably two of the following conditions occur: a) an applied voltage of 0.5 to 200V; and b) the voltage is applied for a duration of 1 second to 60 minutes. In the case of promoting the release of the conductive substrate from the pressure-sensitive adhesive by applying a force (e.g., via a weight or spring), the potential may only need to be applied for about a few seconds. In some embodiments, a potential of 5V for 10 minutes is sufficient to have a debonding effect, and in some embodiments, a potential of 3.5V for 30 minutes is sufficient.
[0112] Desirably, after debonding, the pressure sensitive adhesive composition is on only the first substrate or the second substrate, meaning that one of the substrates is substantially free of adhesive.
[0113] Example
[0114] The following chemicals were used in the examples:
[0115] Duro-Tak 195A from Henkel Corporation
[0116] Duro-Tak AH115 from Henkel Corporation
[0117] Duro-Tak 183 from Henkel Corporation
[0118] 1-Butyl-3-methylimidazolium bis(trifluoromethylsulfonyl)imide (BMIMNTF) from Sigma Aldrich
[0119] Example 1
[0120] The compositions were prepared according to Table 1.
[0121] Table 1
[0122]
[0123] The composition was prepared by mixing the ingredients. The composition was formed into a pressure-sensitive film by applying the composition on a release liner (silicone foil) and then heating at 110° C. for 3 minutes. The prepared PSA film having a thickness of 120 μm was transferred to an aluminum foil (25 mm×200 mm) having a thickness of about 90 μm. A second aluminum foil was pressed onto the PSA film, and a bonded structure ( Figure 2 ). Using a separation speed of 200 mm / min and a sample with an effective area of 2.5 cm×20 cm, a T peel test was performed according to ASTM D1876, and the results are recorded in Table 2.
[0124] Table 2
[0125]
[0126] like Figure 4 As can be seen in the graphs, the bonded structures of Examples 1, 2 and 3 came apart after electrochemical delamination.
[0127] Figure 5 , Figure 6 and Figure 7 All show the force measurement during the measurement as the foil is being pulled apart along the path (in mm) and at the same time the required force (in Newtons) is recorded. Figure 5 The force required to pull apart the aluminum foils bonded together using Example 1 and Comparative Example 4 is shown. Figure 6 The force required to pull apart the aluminum foils bonded together using Example 2 and Comparative Example 5 is shown. Figure 7 The force required to pull apart the aluminum foils bonded together using Example 3 and Comparative Example 6 is shown.
[0128] Example 2
[0129] Different amounts of electrolyte were tested. The compositions were prepared according to Table 3.
[0130] Table 3
[0131]
[0132] The composition was prepared by mixing the ingredients. The composition was formed into a pressure-sensitive film by applying the composition on a release liner (silicone foil) and then heating at 110° C. for 3 minutes. The prepared PSA film having a thickness of 120 μm was transferred to an aluminum foil (25 mm×200 mm) having a thickness of about 80 μm. A second aluminum foil was pressed onto the PSA film, and a bonded structure ( Figure 2 ). The T peel test was performed according to ASTM D1876 using a separation speed of 200 mm / min and a sample with an effective area of 2.5 cm×20 cm. Figure 4 As can be seen in Table 4, the bonded structures of Examples 7-11 came apart after electrochemical delamination.
[0133] Table 4
[0134] Example 7 Example 8 Example 9 Example 10 Embodiment 11 T peeling [N / 25mm] 12.6 14.09 13.25 12.9 14.3 T peeling after electrochemical delamination (20 min, 30 V) 6 4.8 5.3 5.3 3.5
[0135] Example 3
[0136] The stability of the PSA film formed from the composition of Example 7 was tested. The results are reported in Table 7.
[0137] Table 5
[0138] test Example 7 180° peeling N / 25mm steel 15.4 180° peeling N / 25mm glass 15.3 180° Peel N / 25mm Steel (24 hours) 16.3 180° peeling N / 25mm glass (24 hours) 15.4 Loop tack, N / 25mm steel 15 Solid content (60 minutes, 150℃) 43% Static shear test, 25℃, 1kg More than 7 days SAFT Testing Over 200℃
[0139] 180° peel is measured according to FTM-1 in the FINAT Technical Manual 9th edition.
[0140] The ring tack is measured according to DIN EN 1719.
[0141] Static shear is measured according to FTM-8 in the FINAT Technical Manual 9th edition.
[0142] Shear adhesion failure temperature (SAFT) is measured as follows: Instrument ES 07-II (commercially available from Elastocon) is used to test the hot-fail temperature of PSA compositions under shear according to ASTM D4498. Each adhesive member is cut into 25 mm x 25 mm films, which are then laminated on standardized adherends by rolling a 2 kg roller back and forth 2 times at a rate of 10 mm / s. A weight (1 kg) is attached to each member, and the temperature is raised from room temperature at a controlled rate (0.5°C / min) until a temperature of 200°C is reached or the adhesive member fails.
[0143] Figure 8 The force required to pull apart the aluminum foils bonded together using Example 7 is shown.
[0144] The test results illustrate the good stability of the pressure-sensitive adhesive tapes produced from the compositions according to the invention.
Claims
1. A debondable solvent-based pressure-sensitive adhesive composition, comprising: a) (meth)acrylate copolymers, wherein the (meth)acrylate copolymers are formed from monomers selected from the group consisting of ethyl (meth)acrylate, methyl acrylate, butyl (meth)acrylate, 2-ethylhexyl (meth)acrylate, 3-epoxypropyl (meth)acrylate, 2-hydroxyethyl (meth)acrylate, hydrogenated polybutadiene (meth)acrylate, glacial acrylic acid, vinyl acetate, and mixtures thereof; b) an electrolyte selected from the group consisting of 1-butyl-3-methylimidazolium bis(trifluoromethylsulfonyl)imide, 1-ethyl-3-vinylimidazolium methane sulfonate, 1-dodecyl-3-methylimidazolium bis(trifluoromethylsulfonyl)imide, tributyl(ethyl)phosphonium diethyl phosphate, trihexyltetradecylphosphonium bis(trifluoromethylsulfonyl)amide, and mixtures thereof; c) a cross-linking agent; and d) Solvent.
2. The debondable solvent-based pressure-sensitive adhesive composition according to claim 1, wherein: The (meth)acrylate copolymer is present at 23% to 55%, preferably 25% to 40%, more preferably 26% to 39%, based on the total weight of the composition.
3. The debondable solvent-based pressure-sensitive adhesive composition according to claim 1 or 2, wherein: The electrolyte is present at 0.1% to 12%, preferably 0.4% to 11%, more preferably 0.5% to 11%, even more preferably 0.75% to 10.75%, based on the total weight of the composition.
4. The debondable solvent-based pressure-sensitive adhesive composition according to any one of claims 1 to 3, wherein the crosslinking agent is a coordination compound of a metal selected from Al, Ti, Fe, Co, Ba, Zr, K and Zn and an organic compound providing a 1,3-dicarbonyl ligand, preferably the crosslinking agent is selected from aluminum tris-2,4-pentanedionate, diisopropoxybis(acetylacetonate)titanium, and mixtures thereof.
5. The debondable solvent-based pressure-sensitive adhesive composition according to any one of claims 1 to 4, wherein: The crosslinking agent is present at 0.01% to 1.0%, preferably 0.02% to 0.75%, more preferably 0.03% to 0.65%, based on the total weight of the composition.
6. The debondable solvent-based pressure-sensitive adhesive composition according to any one of claims 1 to 5, wherein the solvent is a mixture of two or more solvents, preferably a mixture of three or more solvents, selected from methyl acetate, ethyl acetate, isobutyl acetate, n-butyl acetate, methanol, ethanol, isopropanol, pentanedione, hexane, heptane, toluene, acetone, and mixtures thereof.
7. The debondable solvent-based pressure-sensitive adhesive composition according to any one of claims 1 to 6, wherein: The solvent is present at 43% to 65%, preferably 44% to 62%, more preferably 45% to 60%, based on the total weight of the composition.
8. The debondable solvent-based pressure-sensitive adhesive composition according to any one of claims 1 to 7, further comprising a tackifier, the tackifier is preferably selected from: aliphatic petroleum hydrocarbon resins, alicyclic petroleum hydrocarbon resins, aromatic petroleum hydrocarbon resins and hydrogenated derivatives thereof, polycyclopentadiene resins, hydrogenated polycyclopentadiene resins, aromatic-modified hydrogenated polycyclopentadiene resins; terpenes, aromatic terpenes, hydrogenated terpenes; polyterpenes, aromatic-modified polyterpenes and terpene phenolic resins; copolymers of α-methylstyrene and vinyl aromatic monomers; and gum rosin, gum rosin esters, wood rosin, wood rosin esters, tall oil rosin, tall oil rosin esters and hydrogenated rosin esters; and mixtures thereof, the tackifier is more preferably selected from glycerol esters of partially hydrogenated gum rosin, aliphatic C5 petroleum hydrocarbon resins, and mixtures thereof.
9. The debondable solvent-based pressure-sensitive adhesive composition according to claim 8, wherein: The tackifier is present at 5% to 15%, more preferably 7% to 14%, more preferably 9% to 13%, based on the total weight of the composition.
10. The debondable solvent-based pressure-sensitive adhesive composition according to any one of claims 1 to 9, further comprising a stabilizer, wherein the stabilizer is preferably selected from: 1,3,5-trimethyl-2,4,6-tris(3,5-di-tert-butyl-4-hydroxybenzyl)benzene, pentaerythritol tetrakis-3(3,5-di-tert-butyl-4-hydroxybenzyl)propionate, n-octadecyl-3(3,5-di-tert-butyl-4-hydroxybenzyl)propionate, 4,4'-methylenebis(2,6-tert-butyl)propionate, 4-(tert-butyl)-6-(4-hydroxyphenoxy)-2,4-bis(n-octyl-thio)-1,3,5-triazine, dioctadecyl 3,5-di-tert-butyl-4-hydroxy-benzylphosphonate, 2-(n-octylthio)ethyl 3,5-di-tert-butyl-4-hydroxybenzoate and sorbitol hexa([3-(3,5-di-tert-butyl-4-hydroxyphenyl)-propionate], and mixtures thereof.
11. The debondable solvent-based pressure-sensitive adhesive composition according to claim 10, wherein: The stabilizer is present at 0.05% to 0.25%, more preferably 0.08% to 0.2%, based on the total weight of the composition.
12. A dry film formed from the debondable solvent-based pressure-sensitive adhesive composition according to any one of claims 1 to 11.
13. Use of the debondable solvent-based pressure-sensitive adhesive composition according to any one of claims 1 to 11 or the dry film according to claim 12 in an electronic device.
14. A bonded structure comprising: a) a first substrate having a conductive surface; as well as b) a second substrate having a conductive surface; wherein the debondable solvent-based pressure-sensitive adhesive composition according to any one of claims 1 to 11 or the dry film according to claim 12 is disposed between the first substrate and the conductive surface of the second substrate.
15. A method of debonding a bonded structure according to claim 14, comprising the steps of: 1) applying a voltage across the two surfaces to form an anode interface and a cathode interface, preferably applying a voltage of 0.5 to 200 V for 1 second to 60 minutes; as well as 2) Debonding the surface.
Citation Information
Patent Citations
Electrically disbondable compositions and related methods
US20070269659A1
Electrically Disbonding Adhesive Compositions and Related Methods
US20080196828A1
Electrically disbondable compositions and related methods
US7465492B2
An electrochemically weakable adhesive composition
WO2007142600A1
Electrical debonding of PU hot melt adhesives by use of conductive inks
WO2017133864A1